Immune-Inflammation in Atherosclerosis: A New Twist in an Old Tale - Talepoor, Atefe G.; Fouladseresht, Hamed; Khosropanah, Shahdad; Doroudchi, Mehrnoosh (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background and Objective: Atherosclerosis, a chronic and progressive inflammatory disease, is triggered by the activation of endothelial cells followed by infiltration of innate and adaptive immune cells including monocytes and T cells in arterial walls. Major populations of T cells found in human atherosclerotic lesions are antigen-specific activated CD4+ effectors and/or memory T cells from Th1, Th17, Th2 and Treg subsets. In this review, we will discuss the significance of T cell orchestrated immune inflammation in the development and progression of atherosclerosis. Discussion: Pathogen/oxidative stress/lipid induced primary endothelial wound cannot develop to a full-blown atherosclerotic lesion in the absence of chronically induced inflammation. While the primary inflammatory response might be viewed as a lone innate response, the persistence of such a profound response over time must be (and is) associated with diverse local and systemic T cell responses. The interplay between T cells and innate cells contributes to a phenomenon called immuneinflammation and has an impact on the progression and outcome of the lesion. In recent years immuneinflammation, an old term, has had a comeback in connecting the puzzle pieces of chronic inflammatory diseases. Conclusion: Taking one-step back and looking from afar at the players of immune-inflammation may help us provide a broader perspective of these complicated interactions. This may lead to the identification of new drug targets and the development of new therapies as well as preventative measures.
Keywords: innate cells